Autism, Epilepsy, and Neuroregression: Photosensitivity on Electroencephalography Solved the Riddle. (November 2020) - Madaan, Priyanka; Jauhari, Prashant; Luhar, Zulfiqar M.; Chakrabarty, Biswaroop; Gulati, Sheffali
Autistic epileptiform regression is an uncommon but extensively described malady in children. The clinico-etiological spectrum of this entity ranges from electrical status epilepticus in sleep to various neurogenetic and neurodegenerative disorders. Identification of these disorders is crucial considering their therapeutic and prognostic implications. Simple investigations such as neuroimaging and electroencephalography with activation procedures can provide valuable diagnostic clues in resource-limited settings; facilitating targeted genetic/metabolic testing. Here we report a 3.5-year-old girl with autistic regression and epilepsy. Neuronal ceroid lipofuscinosis was suspected as her electroencephalogram showed photoparoxysmal response on low-frequency (1-3 Hz) intermittent photic stimulation. A deficient leukocyte tripeptidyl peptidase 1 enzyme confirmed the diagnosis of late infantile neuronal ceroid lipofuscinosis.